Закликання весни на Західному Поліссі: жертовна суть обряду - Бойчук, Олена Анатоліївна (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті подано опис закликання весни на Західному Поліссі. Автор у сучасних обрядодіях, пов’язаних із потопленням або спаленням солом’яної ляльки навесні, вбачає відгомони колишніх ритуальних жертвоприношень, зокрема й людських. The Author of the article analyzes ceremonies of invocation of spring on Western Polissya in which sees relic forms of sacrifices. Traces of sacrifice are known since from the Paleolithic, Mesolithic, but ophir, brought in the spring, has distinct agrarian character and corresponds to the Neolithic era. Object of researches is the ceremony of «condacts or exile of Winter», during which drowned or burned a straw effigy doll. Conclusions are made on the basis of the characteristic of the venue of action – near the river. Water from old times is considered one of the addressees of sacrifices. To retains of elements of sacrificial also a material from which is an effigy. In all cases it is straw. It could be used for replacement of the real victim with a profanny being. Also a type of anthropomorphous straw doll which displays historical human sacrifices is an important detail.
Keywords: закликання весни; Західне Полісся; ритуальне жертвоприношення; календарно-обрядовий фольклор; солом'яна лялька; купальський обряд